Cross-country asymmetries in euro area monetary transmission: The role of national financial systems - Hanna Putkuri (Bank of Finland, 2003)
Since 1 January 1999 the ECB has conducted a single monetary policy in the euro area, but the mechanisms by which and the extent to which monetary shocks are transmitted into prices and real economic activity may vary from country to country.This paper investigates how and to what extent the impact of monetary policy depends on national features of financial systems.The main interest is in examining whether the bank lending channel of monetary policy results in asymmetric loan supply reactions on the aggregate level across countries. The variety of transmission mechanisms suggests that the potency of monetary policy may depend on several country-specific factors.On the basis of descriptive analysis, the present Member States seem to differ considerably in terms of their financial systems.The econometric analysis using aggregate data on a panel of twelve countries supports the view that some of these differences may lead to cross-country asymmetries in responses to the common monetary policy.In particular, a larger size and a lower degree of capitalisation of a banking sector are found to strengthen the bank lending channel on the aggregate level.
URN:NBN:fi:bof-20140807207
Keywords: 330; EMU; monetary transmission; bank lending channel; panel data analysis